(6x-9)-(8x+3)=

Simple and best practice solution for (6x-9)-(8x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-9)-(8x+3)= equation:


Simplifying
(6x + -9) + -1(8x + 3) = 0

Reorder the terms:
(-9 + 6x) + -1(8x + 3) = 0

Remove parenthesis around (-9 + 6x)
-9 + 6x + -1(8x + 3) = 0

Reorder the terms:
-9 + 6x + -1(3 + 8x) = 0
-9 + 6x + (3 * -1 + 8x * -1) = 0
-9 + 6x + (-3 + -8x) = 0

Reorder the terms:
-9 + -3 + 6x + -8x = 0

Combine like terms: -9 + -3 = -12
-12 + 6x + -8x = 0

Combine like terms: 6x + -8x = -2x
-12 + -2x = 0

Solving
-12 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -2x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -2x = 0 + 12
-2x = 0 + 12

Combine like terms: 0 + 12 = 12
-2x = 12

Divide each side by '-2'.
x = -6

Simplifying
x = -6

See similar equations:

| 560x^2+5040-5600=0 | | 4(z-5)+6z-1= | | 3(k-16)=15 | | 2(4m+8)-32= | | 2(5x-3)-3(x+5)= | | 24x^2=8 | | 3(5z-6)-4(z+3)= | | (y-8)(y+7)=0 | | x^2+10x+5600=0 | | 4x+45=101 | | -x+7=31x | | x+6x=300 | | -1lnx=0 | | -42+42= | | 3-x=0.5 | | -3p-2(2-5p)=5(p-6)-16 | | X=50(PI-2) | | 85p=4p^2+100 | | -6(3)= | | x^2-53x+240=0 | | p+0.04p=29.12 | | 5y^2=17y+2 | | 126+(-147)= | | 256-16t^2-32=0 | | 1000=3x+x | | 10x^2-33x-106=0 | | 7n-4(5-2n)=20 | | 4-0.5(x+1)=5.6-0.8x | | Tan(x)=2.08 | | 4x(8x)-5y=252 | | 2b+4x= | | 3(2z-6)=18 |

Equations solver categories